Efficacy of Bevacizumab Combined with Paclitaxel and Platinum-Based Chemotherapy in Advanced Metastatic Cervical Cancer and Its Effect on T Lymphocyte Subsets and Tumor Markers - WANG Lijun; ZHAO Hu; YUAN Bo; FANG Ying; WANG Wuliang (Zhongliu Fangzhi Yanjiu, 2023)
Objective To investigate the efficacy of bevacizumab combined with paclitaxel and platinum-based chemotherapy in advanced metastatic cervical cancer and its effect on T lymphocyte subsets and tumor markers. Methods Sixty patients with advanced metastatic cervical cancer (treated in our hospital) were randomly divided into control (30 cases) and treatment (30 cases) groups. All patients were given radiotherapy; the control group received paclitaxel and platinum-based chemotherapy, whereas the treatment group received the same with added bevacizumab. The pain conditions (visual analog score (VAS)) and quality of life (Karl Fischer quality of life (KPS)), clinical efficacy, T lymphocyte subset levels (CD3+, CD4+, and CD8+), tumor markers (carbohydrate antigen 125 (CA125), carcinoembryonic antigen (CEA), and squamous epithelial carcinoma-associated antigen (SCCA)) and adverse reactions were compared between the two groups. Results The VAS score, serum CA125, CEA, SCCA, and CD8+ level were significantly reduced in both groups after treatment (P < 0.05), and it significantly decreased in the treatment group compared with the control group (P < 0.05). KPS score, CD3+, and CD4+ levels significantly increased after treatment in the two groups (P < 0.05), and compared with the control group, the treatment group significantly increased (P < 0.05). Moreover, the total effective rate (66.67%) was significantly higher than that in the control group (40.00%) (P < 0.05), and no significant difference existed in the incidence of adverse reactions between the two groups (P > 0.05). Conclusion Bevacizumab combined with paclitaxel and platinum-based chemotherapy can effectively reduce the pain and improve the immune function and quality of life of patients with advanced metastatic cervical cancer. This chemotherapy is also safe and effective.